2018
DOI: 10.1177/0741932518800807
|View full text |Cite
|
Sign up to set email alerts
|

Response Cards to Increase Engagement and Active Participation of Middle School Students With EBD

Abstract: This study employed an A-B-A-B design to examine engagement and active participation among five middle school students with emotional/behavioral disorders (EBD) while using response cards for mathematics instruction. Students with EBD often exhibit off-task behaviors, which limit their engagement with classroom learning. This is of concern as students with EBD tend to have lower academic achievement compared with their peers and have shown a marked decline particularly in mathematics performance as they move f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…It is critical to understand that the students, which have shown more interest in learning a new course, have mostly been the ones with lesser political activities, and they have been aware of the negative consequences of the wastage of time (12,49,72). The responsibility of the management is not only to provide the course material and the teacher to the students, but it is also the responsibility of the stakeholders to ensure that the students are not involved in different kinds of political activities because they must focus on their productivity (8,12,34,39).…”
Section: Ideological Passion Politically Motivated Internet Addiction...mentioning
confidence: 99%
“…It is critical to understand that the students, which have shown more interest in learning a new course, have mostly been the ones with lesser political activities, and they have been aware of the negative consequences of the wastage of time (12,49,72). The responsibility of the management is not only to provide the course material and the teacher to the students, but it is also the responsibility of the stakeholders to ensure that the students are not involved in different kinds of political activities because they must focus on their productivity (8,12,34,39).…”
Section: Ideological Passion Politically Motivated Internet Addiction...mentioning
confidence: 99%
“…Such cards can be used in various lessons (mathematics, physics, chemistry, sociology, etc. ), as they are a very important, extremely low cost tool (Berrong, Schuster, Morse, & Collins, 2007;Bittinger, 2015;Christle & Schuster, 2003;Clarke, Haydon, Bauer, & Epperly, 2015;Didion, Toste, & Wehby, 2018;Duchaine, Jolivette, Fredrick, & Alberto, 2018;George, 2010;Randolph, 2007). A literature review (Horn, 2010) of six studies evaluated the use of Response Cards specifically for disabled students, and found that use of these cards is an effective strategy that increases the number of students' active responses and their commitment to instructional activities.…”
Section: Implications For Practice and Directions For Future Researchmentioning
confidence: 99%
“…Recent studies have demonstrated electronic Clickers improved (a) on-task behavior and academic performance of middle school students with attention deficit hyperactivity disorder (ADHD) and EBD (Xin & Johnson, 2015), and (b) academic engagement in high school students with EBD (Blood, 2010). Furthermore, researchers recently suggested technology such as Clickers may have an advantage over low-technology options like traditional response cards due to their ability and efficiency in capturing data (Didion, Toste, & Wehby, 2018).…”
Section: Technology and Otrmentioning
confidence: 99%